Wind resource assessment using numerical weather prediction models and multi-criteria decision making technique: case study (Masirah Island, Oman). (1st January 2013) - Al-Yahyai, Sultan; Charabi, Yassine; Al-Badi, Abdullah; Gastli, Adel
The Authority for Electricity Regulation in Oman has recently announced the implementation of a 500 kW wind farm pilot project in Masirah Island. Detailed wind resource assessment is then required to identify the most suitable location for this project. This paper presents wind resource assessment using nested ensemble numerical weather prediction (NWP) model's approach at 2.8 km resolution and multi-criteria decision making (MCDM) technique. A case study based on the proposed approach is conducted over Masirah Island, Oman. The resource assessment over the island was based on the mean wind speed and wind power distribution over the entire island at different heights. In addition, important criteria such as turbulence intensity and peak hour matching are also considered. The NWP model results were verified against the available 10 m wind data observations from the meteorological station in the northern part of the island. The resource assessment criteria were evaluated using MCDM technique to score the locations over the island based on their suitability for wind energy applications. Two MCDM approaches namely equally weighted and differently weighted criteria were implemented in this paper.